Pengaruh Word of Mouth dan Kepuasan Pelanggan Terhadap Keputusan Pembelian Pakaian Wanita Pada Remaja Akhir - Suaidah Lubis; Devi Eka Yulita; Muhammad Syahreza Andrian; Khairun Nisa (Mahesa Research Center, 2023)
The purpose of this study was to determine the effect of word of mouth and customer satisfaction on purchasing decisions. This type of research is quantitative. The population in this study was 222, the research sample was 143 first semester students, the sample was determined using purposive sampling. The data collection instrument used the g-form and was analyzed using SPSS version 20. Data analysis techniques used normality, linearity, multicollinearity, and heteroscedasticity tests. Test the hypothesis using multiple linear regression and T test. Based on the research findings, there is an F count of 113.200 and F table of 3.06. Then F count of 113.200 > 3.06 F table means that Ho is rejected and Ha is accepted. If you see the value of Sig. 0.000 <0.05 then the hypothesis is accepted or in other words there is the influence of word of mouth and consumer satisfaction on purchasing decisions. word of mouth variable (X1) and customer satisfaction variable (X2) simultaneously influence the purchase decision variable (Y) by 61.8%. This research can be developed by linking other variables outside of this research variable.